2009
DOI: 10.1080/10408390802067290
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Vitamins during Extrusion

Abstract: Vitamins (fat and water soluble) are vital food ingredients for healthy living, required by our bodies for normal metabolism. These are present in most natural food in small quantities, but when we process food through thermal processing methods (especially extrusion) a reasonable amount of the present vitamins are lost. During extrusion, factors like barrel temperature, screw rpm, moisture of ingredients, die diameter, and throughput affect the retention of vitamins in food and feed. The vitamins most sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(87 citation statements)
references
References 13 publications
7
77
1
2
Order By: Relevance
“…In general, our recent results (Taciak et al, 2011) on the effects of autoclaving on vitamin B 1 and Ca pantothenate are inconsistent with the conclusions of Riaz et al (2009), who designated vitamin B 1 as sensitive and Ca pantothenate as heat stable during extrusion.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In general, our recent results (Taciak et al, 2011) on the effects of autoclaving on vitamin B 1 and Ca pantothenate are inconsistent with the conclusions of Riaz et al (2009), who designated vitamin B 1 as sensitive and Ca pantothenate as heat stable during extrusion.…”
Section: Discussioncontrasting
confidence: 53%
“…In Taciak et al (2011), the retention of thiamine reached 73% only in a premix autoclaved at 105°C for 10 min, whereas it dropped to 15% and 17% in the premix autoclaved at 121°C for 20 min and 134°C for 10 min, respectively. Also in a study reported by Riaz et al (2009), the effect of temperature on thiamine stability seems to be greater than found in the recent study: high retention of thiamine in feed extruded at 91°C to 95°C declined to 50% when the temperature was raised the range of 141°C to 145°C. According to data presented by Coelho (2002), the destructive effect of temperature on vitamin B 1 depends on its chemical form and is greater on thiamine HCl than on thiamine mononitrate.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…[13][14][15][16][17][18][19] Vitamins may be unstable to heat and light as well as exposure to acid, alkali, air, and moisture. Review of four References 13-16 flagged vitamins unstable in acid, alkali, and on exposure to air (oxygen) and moisture.…”
Section: Spectrum Of Observations-drawn Frommentioning
confidence: 99%